Writing History, Writing Novels: Historical Fiction and Eighteenth-Century Research - Lavoie, Chantel; Miller, Eric (Lumen, 2023)
This article features excerpts from two historical novels set in the eighteenth century, The Boy in the Chimney and The Canada Act, written by Chantel Lavoie of Royal Military College and Eric Miller of the University of Victoria respectively. The novels are inspired in part by the authors’ historical and literary research in eighteenth-century studies. Readings from the novels at the 2022 CSECS conference in Ottawa (Canada), generated a fruitful discussion about turning academic scholarship into fiction. The extracts illustrate the connection between critical and creative writing and show how writing historical fiction can be both a mode of historical analysis and a form of critical engagement with a text or a writer.